SPRAWSTWO ZLECENIODAWCZE JAKO NOWA ZJAWISKOWA FORMA CZYNU ZABRONIONEGO. UWAGI NA TLE PROJEKTU ZMIAN KODEKSU KARNEGO - Pohl, Łukasz (Wydział Prawa i Administracji UAM, 2007)
The paper focuses on a legal analysis of the governmental proposal to add to the catalogue of offences the act o f commissioning a crime (draft article 18 para, la o f the penal code) which, according to the definition in the draft amendment o f the penal code, would consist in commissioning a third party to commit an offence in exchange for a promised financial or personal benefit. In order to justify this legislative proposal, the author has first of all analysed the relations in which this new offence would stand vis a vis other non-executory forms o f offences. The conclusions drawn upon that analysis suggest that the proposed change is not well grounded. The attributes of the act of commissioning a crime do not expand in any way beyond the existing range of acts that are subject to criminalisation as those are already prohibited in the currently binding legal system and, what is more, are also subject to adequate penalisation through sanctioning norms that prohibit the commissioning, as well as incitement or aiding and abetting a crime. Hence the author’s opinion that the amending proposal should be relinquished.
COMMISSIONING A CRIME AS A NEW FORM OF A PROHIBITED ACT. REMARKS ON THE PROPOSED AMENDMENTS OF THE PENAL CODE